Genomic organization and evolution of olfactory receptors and trace amine-associated receptors in channel catfish, Ictalurus punctatus - Gao, Sen; Liu, Shikai; Yao, Jun; Li, Ning; Yuan, Zihao; Zhou, Tao; Li, Qi; Liu, Zhanjiang (Biochimica et biophysica acta. General subjects, 2017)
Channel catfish (Ictalurus punctatus) live in turbid waters with limited visibility to chase prey within a certain distance. This can be compensated through detecting specific water-soluble substances by the olfactory receptors (ORs) and trace amine associated receptors (TAARs) expressed on the olfactory epithelium. We identified the OR and TAAR repertoires in channel catfish, and characterized the genomic organizations of these two gene families by data mining available genomic resources. A total of 47 putative OR genes and 36 putative TAAR genes were identified in the channel catfish genome, including 27 functional OR genes and 28 functional TAAR genes. Phylogenetic and orthogroup analyses were conducted to illustrate the evolutionary dynamics of the vertebrate ORs and TAARs. Collinear analysis revealed the presence of two conserved orthologous blocks that contain OR genes between the catfish genome and zebrafish genome. The complete loss of a conserved motif in fish OR family H may contribute to the divergence of family H from other families. The dN/dS analysis indicated that the highest degree of selection pressure was imposed on TAAR subfamily 14 among all fish ORs and TAARs. The present study provides understanding of the evolutionary dynamics of the two gene families (OR and TAAR) associated with olfaction in channel catfish. This is the first systematic study of ORs and TAARs in catfish, which could provide valuable genomic resources for further investigation of olfactory mechanisms in teleost fish. •The OR and TAAR repertoires in channel catfish were identified and characterized by mining existing genomic resources.•Two conserved orthologous blocks containing OR genes between the genomes of catfish and zebrafish were identified.•The arrangements of conserved motifs within fish ORs and TAARs were generally identical.•The complete loss of a conserved motif in fish OR family H may contribute to its divergence from other families.•The most selection pressures were imposed on fish TAAR subfamily 14 among all genes involved in olfaction.